Bioaktivity Test Crude Fruit of Citrus Lime (Citrus aurantifolia) on Bacteria Escherichia coli in Vitro - Aldino Ramadhianto; Jamilah Nasution (Budapest International Research and Critics University, 2019)
The antimicrobial activity of citrus fruit crude (Citrus aurantifolia) was proven in this experiment with different concentration treatments. The purpose of this study was to determine the antibacterial power of citrus fruit crude against Escherichia coli bacteria tested in vitro. This research uses experimental method with laboratory test for citrus fruit crude using Kirby-baurier of suspectibility test method, with data obtained by using statistical test of Analysis of Varian (Anova) with complete randomized data retrieval. The results showed that of citrus fruit crude has antibacterial power to the growth of Escherichia coli bacteria. At concentrations of 25%, 50%, 75%, 100% formed inhibit zone with an average diameter of 12.6 mm, 15.4 mm, 16.6 mm, 17.3 mm. So, the higher the concentration of citrus fruit crude the better of inhibitory power